Practical and scalable access control mechanism for wireless sensor networks. Issue 1 (21st March 2023) - Khan, Ummer Iqbal; Mir, Ajaz Hussain
The access control mechanism is a necessary security primitive for deploying a new node within the resource-constrained WSN. In literature, new node access control schemes have been proposed for WSN, focusing on efficiency and security strength. However, less attention is given to the functional specification of scalability and independence from time synchronisation. In this paper, an ECC-based new node access control is presented. Besides being computationally effective and secure, the scheme is scalable and doesn't have time synchronisation issues. The proposed scheme's security strength and correctness have been proven using BAN logic and the Random Oracle Model. Simulations on AVISPA and Scyther tools have been performed for automatic security verification of the proposed method. The proposed scheme has also been programmed on TinyOS to perform simulation on the TOSSIM simulator and test-bed implementation on MicaZ motes.